Hourly Surface Observations Suggest Stronger Solar Dimming and Brightening at Sunrise and Sunset Over China - Yawen Wang; Jiahua Zhang; Arturo Sanchez‐Lorenzo; Katsumasa Tanaka; Jörg Trentmann; Wenping Yuan; Martin Wild (Geophysical Research Letters)
Abstract Exploration of the diurnal pattern of global dimming and brightening has been limited by the paucity of high‐temporal resolution observations. Based on 22 years’ continuous observations of hourly surface solar radiation (SSR) over 96 stations across China for 1993–2014, this study evidences higher relative changes in diurnal SSR in terms of both frequency and magnitude at sunrise and sunset, with a longer pathway for the sun passing through the atmosphere, than the hours in between. This, in general, leads to a further shortening of the days between sunrise and sunset in the cold seasons and the polluted region of north China with low radiation levels but a further extension in the other seasons and regions with sufficient sunlight. Pollution reduction by 39.4%–69.7% during the 2014 Asia‐Pacific Economic Cooperation summit at Beijing are accompanied with a 10.4–80.0% rebound of diurnal SSR in the forenoon and late afternoon.